(untitled) (European Journal of Pure and Applied Mathematics, 2017)
The aim of this paper is to show a path to measure a set latent variable through exploratory factorial analysis and confirmatory analysis. It starts with the theoretical mathematical procedure and then, with a database, it shows the re-specified model of study. For data analysis SPSS v.23 and AMOS v.23 statistic software are used. Â Â Â Â Â